Legal issues of protecting the employer's trade secrets - Syrlybayeva, F.M. (Bulletin of the Karaganda University “Law Series”, 2023)
The article defines the measures taken by the employer to protect information constituting a trade secret, the conditions for classifying information as a trade secret. The actions that an employer can take to reduce the internal threat from illegal disclosure of trade secrets are indicated. It is proposed to provide in the employment contract with the head of the organization his obligation to ensure the confidentiality of the information constituting a trade secret, the owner of which is the organization and its counterparties, and responsibility for ensuring the confidentiality of this information. We believe that the condition of the employment contract on non-disclosure of legally protected secrets (state, official, professional or commercial) should be among the mandatory ones in the presence of such types of secrets in the organization and if the employee is admitted to the relevant information in accordance with the procedure established by law. It is also proposed to provide in the Labor Code of the Republic of Kazakhstan a condition on non-disclosure of information constituting a trade secret even after the termination of the employment relationship, as well as the employee's obligation to compensate the employer for damage in case of disclosure of this information. The necessity of developing a set of legal norms is justified, in which it is necessary to determine the limits of the agreements of the parties and the level of compensation for the employee. The author believes that the property interests of the owner of the rights to trade secrets must be protected within the framework of labor legislation, namely, to introduce elements of civil liability, and in the case of disclosure of trade secrets after termination of the employment contract – to bring the employee to civil liability for damages through the court.